Characteristics of Ice Cream Innovation Based On Soy Whey and Dragon Fruit Peel Puree and Its Potential as a Functional Food - Putra, I Gede Arie Mahendra; Wangsaputri, Gabrielle Thasya; Putri, Maria Rosary Mayaranti; Sutisna, Arlin Ramadhan (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2024)
Soy whey is a byproduct derived from tofu production processes. The development of soy whey ice cream could be an innovative product with excellent functional properties. However, the color it produces wasn’t quite as appealing, hence the addition of natural coloring is necessary such as dragon peel fruit. The aimed of this research was to develop soy wey and dragon fruit peel puree, into a functional ice cream product. The research design used Completely Randomized Design (CRD) with five concentration comparisons of soy whey and dragon fruit peel puree i.e. 90:10, 70:30, 50:50, 30:70, and 10:90. Observed parameters include sensory evaluation, overrun, melting time and colors values of L*, a*, and b* as well as antioxidant activity and phenolic total. Data analysis was conducted using ANOVA and followed by the Duncan test of significance (P<0.05). The best treatment used is T5 with the 10:90 ratio. The panelists' acceptance of the treatment were color attribute (slightly liked) resulting in a flirt red color characteristic, aroma attribute (neutral), taste attribute (slightly liked), texture attribute (slightly liked), and overall acceptances (slightly liked). This treatment contains antioxidant activity of 51,84% and 108,83 mg/100 gr of phenolic content. Furthermore, this treatment also produced an ice cream with overrun value of 43.59%, melting time of 38.67 minutes, and the L*, a*, and b* colors values of 41.5; 38.9; and 5.1 with the “flirt red” as a color characteristic.